Identification and properties of a novel clt locus in the Streptomyces phaeochromogenes plasmid pJV1. - Servín-González, L (1996)
A novel clt locus required for efficient transfer of the Streptomyces phaeochromogenes plasmid pJV1 was identified and mapped. The clt region was functional in both orientations, and its absence caused a severe reduction in plasmid transfer. Chromosome mobilization, on the other hand, was not affected by absence of the clt locus. The clt region showed structural, but not sequence, similarity to transfer origins of gram-negative plasmids.